2001
DOI: 10.1128/jb.183.6.2101-2110.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization Function of the pBHR1 Plasmid, a Derivative of the Broad-Host-Range Plasmid pBBR1

Abstract: The pBHR1 plasmid is a derivative of the small (2.6-kb), mobilizable broad-host-range plasmid pBBR1, which was isolated from the gram-negative bacterium Bordetella bronchiseptica (R. Antoine and C. Locht, Mol. Microbiol. 6:1785-1799, 1992). Plasmid pBBR1 consists of two functional cassettes and presents sequence similarities with the transfer origins of several plasmids and mobilizable transposons from gram-positive bacteria. We show that the Mob protein specifically recognizes a 52-bp sequence which contains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 53 publications
2
61
0
1
Order By: Relevance
“…5B). In spite of these similarities, mutation of each of the seven Tyr residues of the pBBR1-Mob protein did not affect the frequency of conjugation of the plasmid, whereas changes at two conserved residues, Asp120 and Glu121, totally abolished plasmid transfer (205). These results leave open the question whether this family of Mob proteins cleaves its target DNA through a Tyr-mediated transesterification reaction or by a water-mediated nucleophilic attack performed by a Glu residue, as proposed for the closing reaction carried out by the replication initiator protein of plasmid pC194 (150).…”
Section: Rcr Mobilizable Plasmids: the Pmv158 Familymentioning
confidence: 99%
See 2 more Smart Citations
“…5B). In spite of these similarities, mutation of each of the seven Tyr residues of the pBBR1-Mob protein did not affect the frequency of conjugation of the plasmid, whereas changes at two conserved residues, Asp120 and Glu121, totally abolished plasmid transfer (205). These results leave open the question whether this family of Mob proteins cleaves its target DNA through a Tyr-mediated transesterification reaction or by a water-mediated nucleophilic attack performed by a Glu residue, as proposed for the closing reaction carried out by the replication initiator protein of plasmid pC194 (150).…”
Section: Rcr Mobilizable Plasmids: the Pmv158 Familymentioning
confidence: 99%
“…Based on the conservation of the N-terminal but not of the C-terminal moiety, it was proposed that the former region of MobM could be involved in the nicking reaction, a hypothesis supported by the conservation of a Tyr residue among the Mob proteins of RCR plasmids (91). For the Mob protein of plasmid pBBR1 (a broad-host-range theta replicating plasmid from the gram-negative host Bordetella bronchiseptica), it was shown that the protein is related to pMV158 MobM (205) and the pBBR1 oriT region has homologies to the pMV158 oriT (Fig. 5B).…”
Section: Rcr Mobilizable Plasmids: the Pmv158 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, in the pIP501 system, relaxase binding to oriT autoregulates the expression of the relaxase and downstream transfer genes (163). Gram-negative plasmid pBBR1 has a nic region identical to that of pMV158, and reminiscent of pIP501, the binding of pBBR1 relaxase at oriT autoregulates downstream tra gene expression (255). It is postulated that this mode of regulation evolved for the feedback control of plasmid transfer rates to minimize the metabolic burden associated with conjugative DNA transfer (163).…”
Section: Gram-positive T4ssmentioning
confidence: 99%
“…In TraA, no putative Leu-zipper motif was found. For Mob, the mobilization protein encoded by the mobilizable broad-host-range plasmid pBBR1, the nic site of which is identical with that of pMV158, autoregulation by the binding of Mob to its promoter region overlapping with oriT has been demonstrated (Szpirer et al, 2001). …”
Section: The Expression Level Of the Tra Genes Is Independent Of Growmentioning
confidence: 99%